Enhancing farm productivity, sustainability, and resilience through farmer participatory integrated farming systems in the arid regions of western Rajasthan - JAT, N K; MEGHWAL, P R; HAJONG, DIPIKA; PARMENDER; N A, VIJAY AVINASHILINGAM (The Indian Journal of Agricultural Sciences, 2025)
A study was carried out during 2021 and 2023 at four villages in Jodhpur, Rajasthan under the ICAR-Farmer FIRST project to assess the productivity, resilience, and sustainability of Integrated Farming Systems (IFS) under rainfed and irrigated conditions in the arid region of western Rajasthan. The study evaluated 15 IFS models (seven rainfed, eight irrigated), of 2.0 ha each. The findings revealed the greater performance of irrigated IFS, which achieved a mean pearl millet (Paspalum scrobiculatum L.) equivalent yield (PEY) of 20,662 kg compared to 7,049 kg in rainfed systems. Enhanced productivity in irrigated IFS was attributed to the inclusion of high-value cash crops such as cumin and onion, alongside innovative components like azolla cultivation and vermicomposting. Economic analysis demonstrated a higher benefit-cost (B:C) ratio for irrigated IFS (3.10) compared to rainfed IFS (2.13), highlighting the economic advantages of resource integration and diversification. Irrigated IFS also exhibited enhanced resource recycling, with significant contributions from crop stover, farmyard manure, and mushroom spent residue. Employment generation was notably higher in IFS systems, providing 271 man-days annually compared to 160 in rainfed IFS systems. Although IFS systems exhibited resilience through resource conservation and stable livestock contributions, their productivity remained constrained by climatic variability. The study highlights the transformative potential of participatory IFS models in optimizing resource use, enhancing farm sustainability and improving livelihoods in resource-scarce arid regions.